2007
DOI: 10.1007/s00023-006-0320-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-Isotropic Cusp Conditions and Regularity of the Electron Density of Molecules at the Nuclei

Abstract: We investigate regularity properties of molecular one-electron densities ρ near the nuclei. In particular we derive a representationwith an explicit function F, only depending on the nuclear charges and the positions of the nuclei, such that μ ∈ C 1,1 (R 3 ), i.e., μ has locally essentially bounded second derivatives. An example constructed using Hydrogenic eigenfunctions shows that this regularity result is sharp. For atomic eigenfunctions which are either even or odd with respect to inversion in the origin, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…A general (optimal) structure-result was obtained recently [2]. For more detailed information, two possible approaches are to study limits when approaching a nucleus under a fixed angle ω ∈ S 2 , as was done in [2], and to study the spherical average of ρ (here denoted ρ ), which is mostly interesting for atoms. The existence of ρ (0), the first derivative of ρ at the nucleus, and the identity ρ (0) = −Z ρ(0) (see (1.12) below) follow immediately from Kato's classical result [12] on the 'Cusp Condition' for the associated eigenfunction (see also [10,15]).…”
Section: Introduction and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A general (optimal) structure-result was obtained recently [2]. For more detailed information, two possible approaches are to study limits when approaching a nucleus under a fixed angle ω ∈ S 2 , as was done in [2], and to study the spherical average of ρ (here denoted ρ ), which is mostly interesting for atoms. The existence of ρ (0), the first derivative of ρ at the nucleus, and the identity ρ (0) = −Z ρ(0) (see (1.12) below) follow immediately from Kato's classical result [12] on the 'Cusp Condition' for the associated eigenfunction (see also [10,15]).…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…That ρ itself is not analytic at the positions of the nuclei is already clear for the groundstate of 'Hydrogenic atoms' (N = 1); in this case, ∇ρ is not even continuous at x = 0. However, as was proved in [2], e Z|x| ρ ∈ C 1,1 (R 3 ).…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…We also assume throughout this paper that the potential V equals to −Z/|r| in the neighborhood of 0, and belongs to C ∞ loc (R 3 \ R) ∩ L 2 # (Ω). It was shown in [23,24,25] that the exact electron densities are analytic away from the nuclei and satisfy certain cusp conditions at the nuclei. The plane wave approximations can not have as good convergence rate as (2.1) due to the cusps at the nuclear positions.…”
Section: Preliminarymentioning
confidence: 99%
“…For eigenvalue problems with singular potentials in full-potential calculations, plane waves are inefficient bases for describing the cusps at the nuclei positions [23,24,25,28]. In contrast, it is observed that a significant part of the rapid oscillations can be captured by atomic orbitals such as Gaussians and Slater-type orbitals [27,34], which have been widely used in quantum chemistry (we refer to [7,18] for their numerical analysis).…”
Section: Introductionmentioning
confidence: 99%
“…We mention only nonlinear Schrödinger equations with selffocusing, density functional models in electron structure calculations (eg. [8,2,4] and the references there), nonlinear parabolic PDEs with critical growth (eg. [15] and the references there, or continuum models of crystalline solids with isolated point defects (eg.…”
Section: Introductionmentioning
confidence: 99%